Property Market Research (SGP 3113)- Quiz II - Mar Iman, Abdul Hamid (2008)
Contains materials in MS Word 2007: Property Market Research (SGP 3113)'s Quiz II. Contents of quiz are based on Chapter 3 - External Environments of Property Market.